Building safer systems by ecological design: using restoration science to develop a medication safety intervention. Issue 2 (31st March 2006) - Marck, P B; Kwan, J A; Preville, B; Reynes, M; Morgan-Eckley, W; Versluys, R; Chivers, L; O'Brien, B; Van der Zalm, J; Swankhuizen, M; Majumdar, S R
Abstract : Background: Experts call for stronger safety cultures and transparent reporting practices to increase medication safety in today's strained healthcare environments. The field of ecological restoration is concerned with the effective, efficient, and sustainable repair and recovery of ecosystems that have been degraded, damaged, or destroyed. A study was undertaken to determine whether the lessons of restoration science can be adapted to the study of medication safety issues. Methods: Working with 26 practitioners, the principles of good restoration were used to design and pilot an innovative multifaceted medication safety intervention. The intervention included focus groups with practitioners, the construction and administration of a research based medication safety inventory, repeat digital photography of environmental safety issues, and targeted environmental modifications. Results: Participants were most concerned about staff education and the physical environment for medication administration. Ward staff used the research to build a healthy reporting culture, introduce regular discussions of near misses, develop education strategies, redesign delivery and storage processes, and renovate the environment. Conclusions: Members of a busy hospital ward successfully adapted methods of restoration science to study, redesign, and strengthen medication safety practices and ward safety culture within existing resources. Further research will be conducted to test the merits of restoration science for health care.